PENINGKATKAN PROFESIONALISME KARYAWAN DALAM MEMENUHI KEPUASAN ANGGOTA STUDI KASUS PADA PRIMER KOPERASI KEPOLISIAN - Mulyanto . (STIE Pelita Nusantara Semarang, 2007)
The business either in services, that is, loananddeposit and the store that have developed unit today can not be considered as a simple business anymore. Since more businessmen have conducted the business above, the competitions to win the consumers are getting more tightly.Based on that matter, the management of the business must perfect a number of strategies constantly to win the competitions. The proper marketing strategies are badly needed to win the competitions to seize the market share. To determine the marketing strategy formulation, w e can not put our attention away from the consumers themselves as the third service users of the above necessity. It is worth noted that without consumers, the operational of a cooperative may not work perfectly.Entering the globalization era is characterized by the profesionalisme. It is urgently needed in order that the qualified human resources available. The member of Primary Police Cooperative (Primkopol) is one of determinant components in conducting the qualified working unit system.However, only professional member of Primery Police Cooperative (Primkopol) in carrying out its mission that will be able to produce qualified outcome.